TRANSLATION OF TEXTS OF POLITICAL DISCOURSE - Zaliesnova Оlena (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The paper is focused on the research of translation peculiarities of the texts of political discourse in the global contemporary information space. Politics is one of the constituents of cultural system of society which possesses high influence on social everyday life. In its turn, a language plays a fundamental role in the process of any political activity, as it makes basis of gaining and holding power, as well as ruling the society. Considering that texts of political discourse are an important instrument of impact on national and international public, it is obvious that they need a detailed analysis and a careful interpretation in transmission to a target language. Texts of political discourse may belong to different genres and possess various stylistic characteristics. From a functional point of view, texts of political discourse have a different aim depending on the type of political activity, being a part or result of it. Among them we define texts of diplomatic discourse, texts of official speech of politicians for certain public of a certain country, and texts of political discourse, the authors of which are not politicians. Texts of political discourse are complex multilayer structures, marked by cultural, ideological and stylistic features, which make translators highly responsible and careful in the transmission of the author’s ideas and messages in other languages. _____________________ References: • Nagorna, P. Politychna mova i movna polityka: diapason mozhlyvoste’ politychnoi lingvistyky [Political language and language policy: the range of possibilities of political linguistics] (Kyiv: Cvitogliad, 2005), 315 (In Ukr.). • Análisis del discurso político, 1ª ed., Rocío Flax [et al.]; edición literaria a cargo de Sara Pérez (Mendoza: Facultad de Filosofía y Letras, Universidad Nacional de Cuyo; Sociedad Argentina de Lingüística, 2014), 97. • Moguel Terol, «Comunicación política en las redes sociales: Análisis del discurso político de ámbito local en medios tradicionales y redes sociales.» Tesis doctoral (Sevilla: Universidad de Sevilla, 2015), 446. • Schaffner, Political discourse analysis from the point of view of translation studies. Journal of language and politics 3(1) (2004): 117-150.